Lithium plus valproate combination therapy versus monotherapy for relapse prevention in bipolar I disorder (BALANCE): a randomised open-label trial - Geddes, JR; Goodwin, GM; Rendell, J; Azorin, J-M; Cipriani, A; Ostacher, MJ; Alder, N; Morriss, R; Juszczak, E (Elsevier, 2009)
Background Lithium carbonate and valproate semisodium are both recommended as monotherapy for prevention of relapse in bipolar disorder, but are not individually fully effective in many patients. If combination therapy with both agents is better than monotherapy, many relapses and consequent disability could be avoided. We aimed to establish whether lithium plus valproate was better than monotherapy with either drug alone for relapse prevention in bipolar I disorder.